Bacterial community succession analysis by next generation sequencing in Changsha city, China. (December 2015) - Guo, J.J.; Liao, H.D.; Fu, X.L.; Zha, L.; Liu, J.S.; Cai, J.F.
Abstract: The estimation of postmortem interval (PMI) is one of the most difficult tasks in forensic practice, especially in putrefied bodies. After death, organisms are decomposed by a variety of enzymes and microorganisms. To investigate the succession of bacterial community in the decomposition process, rat remains were placed outside to decompose under natural conditions in Changsha city, China. Bacterial communities from two regions (buccal cavity and rectum) were sampled when experiment animals were alive, soon after they died and at various time span after death. Bacterial samples were analyzed by high throughput metagenomic sequencing of 16S rRNA gene conducted on an Illumina MiSeq platform. Our data showed that several bacteria genera were potentially useful for estimating the PMI, such as Streptococcus, Ignatzschineria, Acinetobacter, Aggregatibacter, Prevotella and Proteus . There were significant bacterial community structure differences in taxon richness and relative abundance patterns through the decomposition process and across different body sites. As decomposition progressed, a negative linear relationship for taxon richness was found along with a shift from aerobic bacteria to anaerobic bacteria. We first reported the bacterial biodiversity in the decomposition process in Chinese terrestrial scenarios and climatic conditions. Bacteria have a remarkable potential for estimate the PMI and next generation sequencing is a novel method to support the application of bacteria in forensic science.